MODERATING EFFECTS OF FIRM SIZE ON THE RELATIONSHIP BETWEEN PROFITABILITY, LIQUIDITY, AND CAPITAL STRUCTURE: A STUDY ON INDONESIAN REAL ESTATE COMPANIES - Rini Sulistiyowat; Cindy Claudia Oktaviana; Nia Tresnawaty; Efa Wahyuni; Meifida Ilyas (ZILLZELL MEDIA PRIMA, 2026)
This study aims to analyze the effect of profitability and liquidity on capital structure, as well as the moderating role of firm size in the relationship between these variables in real estate companies listed on the Indonesia Stock Exchange during the 2021-2023 period. The data used in this study were obtained from publicly available financial reports. The method employed is panel data regression with the Moderated Regression Analysis (MRA) approach to test the moderating effect of firm size. The results show that profitability does not significantly impact capital structure, while liquidity has a significant negative effect on capital structure. Additionally, firm size was found to moderate the relationship between liquidity and capital structure but does not moderate the effect of profitability on capital structure. This research contributes to the development of capital structure literature in Indonesia's real estate sector and provides practical insights for companies in formulating more effective funding strategies in a dynamic market.